The Effect of Different Types of Directors on the Performance of the Company. - Kanakia, Gina (2010)
The role of the board of directors and their composition is a matter that revolves around different contradictory views for the determination of the performance of the firms. There are several contrasting views that have emerged related to the size of the board and its effect on performance. One set of researchers’ state that larger board size will have diverse skill and knowledge which in turn will have a positive impact on the performance of the firm. The other group of researchers state that a larger board size will have a negative effect on performance due to reasons like lack of coordination, slow decision making process and free rider issues. The third group states that the relationship between the size of the board and the performance of the firm is in form of an inverted U shaped curve. While some other researchers find low significance or no link between the board size and the performance of the firm. The researcher has thus formed the first and the third hypothesis based on these contradictory views. Based on the contradictory opinions regarding the number of non-executive directors and their effect on performance of the firm the researcher has set the second hypothesis for this dissertation. There are three groups of researchers that study the effect of non-executive directors and their impact on the performance of the firm. One of them state that there is a positive impact on performance, the other state that there is a negative influence due to the outside directors and the third find no relation between the non-executive directors and the performance of the firms. This dissertation studies these issues, uses quantitative method to study the effect between variables, explains the vagueness in data obtained, discusses the findings and mentions the inferences and the implications formed out of this dissertation.